UI/UX Implementation for Junior High Adventure Game using UCD Method in P5 Project - Deuis Nur Astrida; M. Syaiful Amin; Arifudin, Dani (Journal of Informatics and Interactive Technology, 2024)
One of the activities in the independent learning curriculum is thePancasila Student Profile Strengthening Project (P5), a project-basedco-curricular activity aimed at enhancing competence and characteraccording to the Pancasila learner profile, based on GraduationCompetency Standards. One theme of the P5 project is engineeringand technology, where students create innovative works usingtechnology to solve problems in their educational environment, suchas environmental pollution and limited educational resources. Anexample outcome is the adventure game "The Ghost," designed tofoster students' creativity in digital production, not just as users. Giventhe high rate of game addiction among students, this project isparticularly relevant.The study utilized the User Centered Design (UCD) methodology todevelop and assess the usability of the "The Ghost" user interface,created with Construct 2. The UCD process comprised user research,design, prototyping, and testing stages. Initial user research involvedsurveys and interviews to gather user needs and preferences. Theseinsights informed the design stage, where user interface prototypeswere created and refined iteratively based on feedback. In the testingstage, usability was evaluated with real users who performed tasks andcompleted the System Usability Scale (SUS) questionnaire. The gamewas tested on Android devices, and the results showed that it is highlyusable, with 85% of respondents rating it positively, and an intervalscale score of 77.68 classifying the application as good andentertaining. Additionally, the game ran smoothly on Android, furthervalidating its usability and performance.